2020
DOI: 10.1093/jac/dkz561
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of viral load suppression, predictors of virological failure and patterns of HIV drug resistance after 12 and 48 months on first-line antiretroviral therapy: a national cross-sectional survey in Uganda

Abstract: Objectives We implemented the WHO cross-sectional survey protocol to determine rates of HIV viral load (VL) suppression (VLS), and weighted prevalence, predictors and patterns of acquired drug resistance (ADR) in individuals with virological failure (VF) defined as VL ≥1000 copies/mL. Methods We enrolled 547 and 1064 adult participants on first-line ART for 12 (±3) months (ADR12) and ≥48 months (ADR48), respectively. Dried bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…The value of viral suppression in this study was also higher compared to 79% reported in a multi-center Nigerian study [ 8 ], and 84% in Borno state, north-eastern Nigeria [ 9 ], 69% in Ghana [ 10 ] and 73% in northern Ethiopia [ 11 ]. High level of viral suppression in this study are comparable with the reports from Uganda where a level of 95% was observed for viral suppression after 12 months of HAART among PLHIV [ 12 ]. Similarly, the level of viral non-suppression obtained in this study is comparable to 9.0% and 7.0% reported in the African cohort study [ 13 ], and Vietnam [ 14 ] respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The value of viral suppression in this study was also higher compared to 79% reported in a multi-center Nigerian study [ 8 ], and 84% in Borno state, north-eastern Nigeria [ 9 ], 69% in Ghana [ 10 ] and 73% in northern Ethiopia [ 11 ]. High level of viral suppression in this study are comparable with the reports from Uganda where a level of 95% was observed for viral suppression after 12 months of HAART among PLHIV [ 12 ]. Similarly, the level of viral non-suppression obtained in this study is comparable to 9.0% and 7.0% reported in the African cohort study [ 13 ], and Vietnam [ 14 ] respectively.…”
Section: Discussionsupporting
confidence: 89%
“…The value of viral suppression in this study is also higher compared with 79% in a multi-center Nigerian study [8], and 84% in Borno state in north-eastern Nigeria [9], 69% in Ghana [10] and 73% in northern Ethiopia [11]. Our findings of a high level of viral suppression are comparable with the reports from Uganda where a level viral suppression of 95% was observed after 12 months of HAART among PLHIV [12]. Similarly, the level of viral non-suppression obtained in this study is comparable to 9.0% reported in the African cohort study [13], and 7.0% reported in Vietnam [14] after at least 12 months of HAART.…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, in our study, a substantial proportion of both DBS and plasma specimens had VL<10,000 copies/mL. This implies that in this era when virological suppression (VL<1000 copies/mL) rates nearing or exceeding 90% have been observed [36,40], and following recommendations to use more potent dolutegravir-containing regimens, genotyping success rates are likely to continue to decline. There is evidence in this study that shows median viral loads of specimens analysed in our laboratory rapidly decreasing from 2016 to 2019.…”
Section: Discussionmentioning
confidence: 60%
“…There is evidence in this study that shows median viral loads of specimens analysed in our laboratory rapidly decreasing from 2016 to 2019. This can be explained by rapid scale-up of ART following recommendations of the WHO and subsequent high VL suppression rates reported in our setting [40]. What is more intriguing is that even at VL<1000 copies/mL, HIVDR variants can still be selected as reported in a Kenyan study in which plasma samples with VL£1000 copies/mL had a genotyping success rate of 32% [49].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation